Impact of corporate governance and ownership concentrations on timelines of financial reporting in Pakistan - Muhammad Waris; Badariah Haji Din (Cogent Business & Management)
The objective of this paper is to explore the relationship among corporate governance, timelines of financial reporting and ownership concentration taken as a moderating effect among the listed firms on Pakistan Stock Exchange. In this study, we developed hypothesis about the relationship between corporate governance and timelines of financial reporting by using the data of 100 listed firms during the period of 2013 to 2017. By applying ordinary least squares, we find out that auditor brand name decreases the audit report lag and increases the quality of the audit. Audit opinion also has an impact on the audit quality if there is an unqualified report, and then the quality of the audit increases with decrease in lags. A large number of board meeting decreases the lags and increases the audit quality. Independent board decreases the lags and increases the audit quality. Family ownership, the most important variable, decreases the management report lag and increases the audit quality. If ownership concentration is taken as a moderator, then board diligence has a negative relationship with the timelines that show the large number of board meeting decreases the lags and increases the audit quality. The board size is positively related with timelines, which means that larger board increases the lags and the audit quality decreases. The audit committee presence decreases the management report lag and without moderating, the audit committee has no impact on the timelines. However, some hypotheses are fully supported, and some partially support the relationship. Our finding is that corporate governance has an impact on timelines of financial reporting and ownership concentration has moderating effect that enhances the relationship.